Demonstrating the Use of Linked Data to Advance Education Research - Porter, Sonya R; Pharris-Ciurej, Nick; Penner, Emily; Brummet, Quentin (International Journal of Population Data Science, 2018)
Linking K-12 data on students and teachers to Internal Revenue Service (IRS) information allows us to answer questions that are difficult to answer using survey data or educational administrative data alone. We describe two research projects that demonstrate the importance of using linked administrative data to further research on education and inform policy discussions. In the first research project, using linked IRS income tax data to school administrative records for all 8th graders in one California public school district and all K-12th graders in Oregon public schools, we examine how well free and reduced price lunch (FRPL) enrollment captures student disadvantage. We find that FRPL categories capture relatively little variation in household income. However, FRPL captures elements of educational disadvantage that IRS-reported household income data do not. In the second research project, using data on teachers from a large California school district linked to IRS records and the Business Register, we examine what teachers do after they leave teaching. Preliminary findings suggest that many teachers leave the workforce after they leave teaching. Teachers that continue to work after leaving our school district often do so in a nearby school district, and often see a modest increase in their earnings in their new positions.